There's a Lemma concerning properties of rings I have to prove.

Prove the following properties of a ring $\langle R; +,-,0,\cdot,1\rangle$ and $a,b \in R$:

(iv)$\hspace{2.55em}$ If $R$ is non-trivial (i.e., if it has more than one element), then $1≠0$.

The exercises says that I'm allowed to use the statement (i) without proof.

My attempt for (ii):
Assumption 1 is in R:
$(-1)(-1) + (-1) = 0 = (1) + (-1)$ which is $(-1)^2 = (1)$? Is that even a proof?

I don't know about the other statements though.

Thanks I advance. I really appreciate it.

  • $\begingroup$ By the way, (i) can be proved as well. Since $0 = 0+0$, $0a = (0+0)a = 0a + 0a$, which implies $0a = 0$. The other equality $a0 = 0$ can be proved similarly. $\endgroup$ – aras Nov 22 '15 at 13:54

It is quite unclear to me what you are trying to do there, in particular it seems you want to use $(-1)(-1)=1$ which is a special case of what you should show in (iii). Moreover, there is no need to assume $1$ is in $R$, it appears your definition enforces this.

Now, to show (ii) it can be a good idea to get clear what is even written there, it seems so natural that it can be hard to see what the point is.

Note that $-ab$ is the additive inverse of $ab$, while $(-a)b$ is the product of $-a$, the additive inverse of $a$, and $b$.

You need to show that the additive inverse of $ab$ is $(-a)b$. Thus add $ab$ and $(-a)b$ and see if you get $0$. If this is true, then you have shown that $(-a)b$ is the additive inverse of $ab$, that is $-ab$. (This assumes you know already that an additive inverse is unique.)

To see this note $ab +(-a)b = (a+(-a))b = 0 b = 0$, where you used the distributive law and (i).

For (iii) you basically use (ii) twice (and the fact that $-(-c)=c$).

For (iv), take any $a$ in $R$. Then if $1 = 0$ then of course $1a = 0 a$. But the former is $a$ (by definition of $1$) while the latter is $0$ by (i). Thus you get $a= 0 $ for all $a$ in $R$, that is the ring is trivial.


(ii) $(-a)b=-(ab) \Leftrightarrow (-a)b+ab=0 \Leftrightarrow ((-a)+a)b=0 \Leftrightarrow 0·b=0$ which is true by (i)

(iii) $(-a)(-b)=-a(-b)$ by (ii). But $-a(-b)=ab \Leftrightarrow ab+a(-b)=0 \Leftrightarrow a(b+(-b))=0 \Leftrightarrow a·0=0$ which is true by (i)

(iv) If $R$ is non trivial $\exists a\in R-\{0\}$. Then $(1·a)-a=0$. If $1=0$ then $1·a=0$ and hence $-a=0 \Leftrightarrow a=0$ which is not true.

We used the definition of $-a$, which is:

$-a$ is an element of $R$ such that $a+(-a)=0$


Hint for (ii): show that $ab$ is the additive inverse of the RHS and the LHS. By uniqueness of inverses (you probably will have seen the proof of this), RHS = LHS.

Hint for (iii): Use (ii).

Hint for (iv): Prove the contrapositive. Let $R$ be a ring where $0=1$ and pick a $x \in R$. You should use the fact that $0=1$ to show that $R$ is trivial.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.